Revisão sistemática dos efeitos biológicos de hyptolactonas e investigação do potencial antibacteriano de metabólitos secundários isolados de Hyptis pectinata (L.) Poit. frente a Streptococcus pyogenes - Julião, Felipe Gabriel Henrique (2022)
Hyptis pectinata (L.) Poit. (Lamiaceae), popularly known in Brazil as “sambacaitá” or “canudinho”, it is a plant used in folk medicine to treat inflammation, infections, pain and tumors. Among the bioactive substances present in the species, highlighted, the hyptolide and pectinolides, secondary metabolites of the hyptolactone class. The structural similarity of some hypolactones to pironetin, a natural product with increased cytotoxic effects, leads us to believe that these substances have great biological potential. Based on this, a bibliographic survey was carried out through a systematic review of hyptolactones and their biological activities in different databases. Of the 86 hyptolactones isolated from plants and fungi, 57 showed mainly cytotoxic, antibacterial, and antifungal activity against cancer cells. In view of the results found, this study aimed to isolate pectinolides and hyptolide, and for the first time, evaluate their effect against Streptococcus pyogenes, the bacterium responsible for causing throat infection. The crude extracts of leaves and inflorescences of H. pectinata were submitted to liquid-liquid partition and the dichloromethane fractions were submitted to classical liquid chromatography to obtain fractions enriched in hyptolide and pectinolides (FEHP). These fractions were analyzed by high-performance liquid chromatography (HPLC) and their substances isolated by HPLC. After elucidating the chemical structures by nuclear magnetic resonance and mass spectrometry, the FEHP and the isolated substances: hyptolide, pectinolides E, G and Q (inedited) were evaluated against S. pyogenes. The FEHP from leaves and inflorescences showed minimum inhibitory concentration (MIC) of 64 µg/mL and minimum bactericidal concentration (MBC) of 256 and 512 µg/mL, respectively. Pectinolides E and G had a MIC of 256 µg/mL, however, only pectinolide G was bactericidal at this concentration. The evidence generated in this study, together with the existing results of the cytotoxic and antibacterial effect of these substances and other hyptolactones, allow hyptolide and pectinolides to further expand their potential, with chances of becoming prototypes for drugs that must be proven from further studies.